The incidence of Japanese encephalitis in Taiwan--a population-based study. - Li-Ching Hsu; Yu-Ju Chen; Feng-Kuang Hsu; Jyh-Hsiung Huang; Chi-Ming Chang; Pesus Chou; I-Feng Lin; Feng-Yee Chang (Public Library of Science (PLoS), 2014)
A mass Japanese encephalitis (JE) vaccination program targeting children was launched in Taiwan in 1968, and the number of pediatric JE cases substantially decreased thereafter. The aim of this study was to elucidate the long-term trend of JE incidence, and to investigate the age-specific seroprevalence of JE-neutralizing antibodies.A total of 2,948 laboratory-confirmed JE cases that occurred between 1966 and 2012 were analyzed using a mandatory notification system managed by the Centers for Disease Control, Taiwan. A total of 6,594 randomly-sampled serum specimens obtained in a nationwide population-based survey in 2002 were analyzed to estimate the seroprevalence of JE-neutralizing antibodies in the general population. The average annual JE incidence rate of the group aged 30 years and older was 0.167 cases per 100,000 people between 2001 and 2012, which was higher than the 0.052 cases per 100,000 people among those aged under 30 years. These seroepidemiological findings indicate that the cohort born between 1963 and 1975, who generally received two or three doses of the vaccine and were administered the last booster dose more than 20 years ago, exhibited the lowest positive rate of JE-neutralizing antibodies (54%). The highest and second highest antibody rates were observed, respectively, in the oldest unvaccinated cohort (86%) and in the youngest cohort born between 1981 and 1986, who received four doses 10-15 years ago (74%).Over the past decade, the main age group of the confirmed JE cases in Taiwan shifted from young children to adults over 30 years of age. People who were born between 1963 and 1975 exhibited the lowest seroprevalence of JE-neutralizing antibodies. Thus, the key issue for JE control in Taiwan is to reduce adult JE cases through a cost-effective analysis of various immunization strategies.